Learning in pairs, thinking in shapes: A study on spatial reasoning in elementary school - Lingga Nico Pradana; Octarina Hidayatus Sholikhah; Joel I. Alvarez (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study examines the effectiveness of the Power of Two learning model in improving fifth-grade students’ spatial reasoning skills, specifically in understanding plane figures and composite areas. A quantitative approach was employed using an Interrupted Time Series Design, involving 29 students from a public elementary school. The instrument used was the VR-test (Visualization and Relation Test), designed to measure two components of spatial reasoning: spatial visualization and spatial relation. The test was administered in two phases: a pre-test before the intervention and a post-test afterward. The pre-test assessed students’ initial ability to identify and calculate the area of shapes that form composite figures. After the Power of Two intervention, students showed an increase in their average post-test scores, indicating improved spatial reasoning. Statistical analysis using paired and independent-samples t-tests revealed significant differences between pre- and post-test results, confirming the intervention's effectiveness. The findings also demonstrated that both male and female students improved, although males slightly outperformed females in spatial visualization and spatial relations. Furthermore, the study highlights the pedagogical potential of peer collaboration and structured dialogue in developing students’ spatial thinking. These findings provide empirical support for integrating cooperative learning models, such as the Power of Two, into elementary mathematics instruction.